2021
DOI: 10.1002/jclp.23224
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effect of mental contamination and cognitive fusion on anxiety

Abstract: Objectives Mental contamination and cognitive fusion have been identified as risk factors for anxiety. The purpose of this study was to examine the moderating effect of cognitive fusion on the relationship between mental contamination and anxiety. Method Participants (N = 504 community adults), recruited via Amazon's Mechanical Turk (MTurk), completed measures of mental contamination, cognitive fusion, and anxiety. Results Results from a regression analysis showed that the interaction between mental contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Throughout the COVID-19 pandemic, cognitive fusion, characterized as an over-identification with thoughts and an inability to distract oneself from them, has been found to be a clear precipitator of negative psychoemotional consequences on HCWs [ 41 ]. Its relationship to consequences of work-related stressors, such as anxiety, has also been previously studied [ 24 ]. Our results, in the absence of previous studies, show its role as a risk factor for insomnia, increasing symptoms at short-, medium- and long-term stages of the COVID-19 pandemic and affecting its evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the COVID-19 pandemic, cognitive fusion, characterized as an over-identification with thoughts and an inability to distract oneself from them, has been found to be a clear precipitator of negative psychoemotional consequences on HCWs [ 41 ]. Its relationship to consequences of work-related stressors, such as anxiety, has also been previously studied [ 24 ]. Our results, in the absence of previous studies, show its role as a risk factor for insomnia, increasing symptoms at short-, medium- and long-term stages of the COVID-19 pandemic and affecting its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other studies have found a clear negative relationship between resilience and insomnia [ 23 ]. Cognitive fusion has also been studied in HCWs, suggesting a clear relationship with anxiety [ 24 ]; however, its relationship with insomnia has not been studied either.…”
Section: Introductionmentioning
confidence: 99%
“…An implication of the psychological inflexibility model is that cognitive fusion and experiential avoidance are crucial toxic mechanisms that connect stressful factors with mental health problems (Hayes et al, 2012). Some studies have demonstrated the effect of cognitive fusion or experiential avoidance from a moderator perspective (e.g., Bardeen & Fergus, 2016; Clauss & Bardeen, 2022; Hekmati et al, 2023; Tyndall et al, 2018); however, in the association of stress with psychological problems, the mediating roles of these two processes seem to receive more empirical support. Cognitive fusion has been found to mediate the association of occupational stressors (Zhang et al, 2021), stigma (Valvano et al, 2016), and pain intensity (Carvalho et al, 2019) with psychological symptoms including depression.…”
Section: The Possible Mediating Effects Of Cognitive Fusion and Exper...mentioning
confidence: 99%